Origine, âge et taux d’accrétion verticale de la tourbière à palses de Blanc-Sablon, basse Côte-Nord, Golfe du Saint-Laurent, Québec - Dionne, Jean-Claude; Richard, Pierre J.H. (Géographie physique et Quaternaire, 2006)
The palsa peat bog in the Blanc-Sablon area was formed in a lacustrine basin isolated by a moraine ridge at the head of the Blanc-Sablon River valley when the isostatic land recovery reached the 60-70 m level. At the beginning, the depth of the lake was about 10 m however, the lake was soon drained almost entirely about 10 200 years ago (around 9 ka 14C BP) when the Blanc-Sablon River cut back the moraine ridge. The floor of the resulting shallow lagoon was then progressively covered by an aquatic plant species carpet. Peat began to grow and accumulate about 9400 yr BP (8,4 ka 14C BP), and finally the peat reached about 3 m in thickness. At the section studied, the peat carpet is made of two main layers of sphagnum separated by a layer of fen peat. At this site, the vertical accretion of the peat could have reached 2-3 mm per year, the average being 0.53 mm/yr between 9400 and 4400 yr BP (8,4 to 4 ka 14C BP), until a fire occurred. Radiocarbon age at the surface of the thick sphagnum layer overlying the fire event is about 500 years BP whereas the thin and dry lichen layer at the surface date back only 40 ± 60 14C yr BP. However, in two sites located in the peat bog center, the peat layers under the lichens have been dated from modern to 2330 cal yr BP (2280 ± 60 14C yr BP). Consequently the apparent slow down in peat accumulation after the fire shown at the studied section is likely due to the local build-up of the palsa. The mean vertical accretion rate for the 3 m thick peat carpet is about 0.32 mm/yr. Permafrost probably occurred into the peat bog about 500 years ago, during the Little Ice Age. La tourbière à palses de Blanc-Sablon s’est formée dans une cuvette lacustre isolée par un cordon morainique lors de l’émersion des terres au niveau de 60-70 m. D’une dizaine de mètres de profondeur au début, le lac s’est vite transformé en une lagune lorsqu’il s’est vidangé il y a 10 200 ans environ (vers 9 ka 14C BP) suite à l’incision du cordon morainique par recul de tête de la rivière Blanc-Sablon ou par son ...